2016
DOI: 10.1096/fj.201600613r
|View full text |Cite
|
Sign up to set email alerts
|

Adverse left ventricular remodeling by glycoprotein nonmetastatic melanoma protein B in myocardial infarction

Abstract: Cardiac diseases are the leading cause of death. Available treatment approaches are not sufficient to reverse persistent cardiac damage after injury; thus, the search for new therapeutic targets is essential. Our microarray-based screening in rat hearts 24 h after myocardial infarction (MI) yielded glycoprotein nonmetastatic melanoma protein B (GPNMB), which is known to be involved in inflammation and fibrosis after tissue injury. However, its role in the heart was elusive. We found increased cardiac expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 64 publications
(98 reference statements)
1
19
0
Order By: Relevance
“…A subtle difference could be attributed to strain, age, sex, or housing-condition differences (see Transparent Methods ). The validity of the datasets was further confirmed by the regulated expressions of the known disease marker genes ( Bosworth and de Boer, 2013 , Cheng et al., 2015 , Hiratsuka et al., 2006 , Jarve et al., 2017 , Pabla et al., 2015 , Port et al., 2011 , Ramesh and Reeves, 2002 , Reed et al., 2011 , Sehl et al., 2000 , Suyama et al., 2012 , Tonne et al., 2013 , Wada et al., 2016 ) ( Figure 2 ). To evaluate how broadly the gene expressions are altered across various organs, we compared both model and sham control with WT control datasets independently using DESeq2 analysis.…”
Section: Resultsmentioning
confidence: 76%
“…A subtle difference could be attributed to strain, age, sex, or housing-condition differences (see Transparent Methods ). The validity of the datasets was further confirmed by the regulated expressions of the known disease marker genes ( Bosworth and de Boer, 2013 , Cheng et al., 2015 , Hiratsuka et al., 2006 , Jarve et al., 2017 , Pabla et al., 2015 , Port et al., 2011 , Ramesh and Reeves, 2002 , Reed et al., 2011 , Sehl et al., 2000 , Suyama et al., 2012 , Tonne et al., 2013 , Wada et al., 2016 ) ( Figure 2 ). To evaluate how broadly the gene expressions are altered across various organs, we compared both model and sham control with WT control datasets independently using DESeq2 analysis.…”
Section: Resultsmentioning
confidence: 76%
“…This protein, also called osteoactivin, DC-HIL, or hematopoietic growth factor inducible neurokinin-1, has been studied extensively in many contexts including cancer, kidney injury, obesity, non-alcoholic steatohepatitis, Parkinson disease, osteoarthritis, lysosome storage disorders, and heart failure; and, in most of these contexts expression of GPNMB is induced by the related pathology, likely in response to lysosomal stress[12, 2227]. However, loss of Gpnmb expression in DBA/2J mice is associated with preserved cardiac function after myocardial infarction[28]. Thus, there is much interest in Gpnmb and the role it plays in a multitude of diseases and in normal physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using different cardiac injury models have shown that cardiac tissue levels of GPNMB generally increased in response to stress. These include the desmin knockout mouse model ( Psarras, Mavroidis et al 2012 ), the Theiler’s murine encephalomyelitis virus-induced acute viral myocarditis model ( Omura, Kawai et al 2014 ), and the myocardial infarction rat and mouse models ( Järve et al 2017 ). In the myocardial infarction model, GPNMB mRNA transcript was up-regulated 17-fold in the peri-infarct (PI) area in the rat and 300-fold in the mouse at 24 hr and 7 days after myocardial infarction, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We investigate a novel potential HF biomarker, Glycoprotein NMB (GPNMB), in both mice and humans. GPNMB is a type 1 transmembrane protein also known as osteoactivin ( Selim 2009 ) that has been recently involved in inflammation, fibrosis and myocardial remodeling ( Järve et al 2017 ).…”
mentioning
confidence: 99%